The magnetic, optical and electronic properties of Mn–X(X = O, Se, Te, Po) co-doped MoS2 monolayers via first principle calculation - Qi-Zhi Lang; Yan-Bin Huang; Jie-Min Wei; Yi Wang; Xiang Guo; Zi-Jiang Luo; Zhao Ding (Materials Research Express, 2020)
The magnetic and optical properties studies in monolayer transition-metal dichalcogenides have attracted attention because of the manufacture spintronic, electronic and photonic devices. This paper reported the magnetism and optical properties of Mn–O, Mn–Se, Mn–Te, Mn–Po co-doped MoS _2 monolayer systems via first principle calculation, results show Mn-X(X = O, Se, Te and Po) co-doped MoS _2 monolayer systems appear half-metal (HM) ferromagnet, their corresponding magnetic moments are 1.06 μ _B , 1.04 μ _B , 1.04 μ _B , 1.03 μ _B , respectively. Co-doped systems have smaller band gaps due to effective charge compensation among Mn–O, Mn–Se, Mn–Te and Mn–Po atoms. According to calculation, we find Mn–O co-doped MoS _2 monolayer has the lowest formation energy in four co-doping systems. Thus the Mn–O co-doped MoS _2 monolayer has the best stability. The Mn–Se co-doped MoS _2 monolayer has the highest static dielectric constants ${ε }_{1}\left(ω \right)$ and ${ε }_{2}\left(ω \right),$ refractive index $n\left(ω \right)$ and $k\left(ω \right).$ In energy range of 0 to 1.5 eV, the transmittance of intrinsic MoS _2 system is higher than that of all co-doped MoS _2 systems obtained by absorption coefficient $α \left(ω \right).$